Re-engineering of business processes on the example of enterprise - Ермекова, Ж. (Journal of Economic Research & Business Administration, 2017)
The word of the radical changes in the economy there is an urgent need for new tools and techniques that can help organizations become more efficient. Reengineering is one of the most modern tools of this type. Foreign companies are often faced with such problems, the solution of which with the help of traditional knowledge and management paradigms, and it is practically impossible. In view of this, more and more managers are looking for new and innovative ways to achieve concurrency privileges. Appeal to reengineering due to the need to develop a fundamentally new business model. Attract public attention to the ideas and practices reengineering due not least to the entry of the world economy in the era of ubiquitous of application of information technology-based mass computerization and use of information technology. The degree of efficiency of the organization undoubtedly is largely dependent on the effective implementation of its business processes